Effect of ABA on colour of berries, anthocyanin accumulation and total phenolic compounds of 'Rubi' table grape (Vitis vinifera) - Neto, Francisco José Domingues [UNESP]; Tecchio, Marco Antonio [UNESP]; Junior, Adilson Pimentel [UNESP]; Vedoato, Bruna Thais Ferracioli [UNESP]; Lima, Giuseppina Pace Pereira [UNESP]; Roberto, Sergio Ruffo (Southern Cross Publishing, 2017)
The color of the berry grapes is due to existence of anthocyanins and their accumulation seems to be regulated, at least in part, by abscisic acid. Therefore, exogenous applications of this regulator may increase the anthocyanins concentration in the grapes skin. The objective of this study was to evaluate the effect of abscisic acid on the color of berries and in the anthocyanin accumulation and total phenolic compounds of 'Rubi' grapes. The 'Rubi' grape (Vitis vinifera) variety was studied in the sixth year of production. The experimental design was randomized blocks, with 4 treatments and 6 replications. The treatments consisted of isomer concentrations of (S)-cis-abscisic acid (S-ABA), as follow: Control (0 mg L -1); 400 mg L-1 de S- ABA at the beginning of the maturation (BM); 400 mg L-1 at BM + 200 mg L-1 at 25 DAFA (25 days after the first application) and 400 mg L-1 in BM + 400 mg L-1 at 25 DAFA. The berry bunches were sprayed in the morning, using costal sprayer providing full and uniform coverage. The colorimetric characteristics were determined with colorimeter obtaining the following variables: luminosity, saturation, hue angle and color index. The fresh mass, length and width of bunch (berries and stems), number of berries per bunch, soluble solids, titratable acidity, soluble solids/acidity ratio, pH, reducing sugars, anthocyanins, and phenolic compounds were evaluated. The abscisic acid (S-ABA) promoted the physical characteristics of the bunch and berries slightly with no effect on the stems. However, it triggered significant increase in soluble solids content and in the soluble solids/acidity ratio. It also increased the anthocyanin and total phenolic compounds, especially when applied twice, regardless of the concentration, in addition to improve color attributes. It is recommended the application of 400 mg L-1 at BM + 200 mg L-1 at 25 DAFA can be useful to increase anthocyanin and total phenolic and to improve color attributes.
Keywords: Biochemistry; Color index; Plant physiology; S-ABA; Vitis vinifera L.